Action of S³ on Homotopy 15-Spheres - Naoum, Adill; Dawood, Nerjis (Iraqi Journal of Science, 2025)
In this paper, we establish a relation between differential S’ actions on homotopy 15-spheres and (12, 7) sphere pairs.